Hubungan Konsumsi Pangan Hewani Dengan Status Gizi Anak SD Negeri Kudu 02 Kecamatan Baki Kabupaten Sukoharjo - ARDHYATI, Yana Ayu; , Susi Dyah Puspowati, SP., M.Si; , Luluk Ria Rakhma, S.Gz., M.Gizi (2015)
Background : Short and very short are nutritional status based on the index Height/Age. Short on children is the result of a shortage of food nutrients. Animal based food contains energy, protein, vitamin A, and Fe better than vegetable food. The content of these nutrients necessary for bone growth in children. Purpose : This study aimed to determine the relationship between consumption of food with nutritional status of elementary school children of Kudu 02 Baki Subdistrict Sukoharjo Regency. Research Method : This research is a descriptive research with cross sectional method. The number of research subjects as much as 35 selected by simple random sampling. Animal food consumption data obtained from the 24-hour recall data and nutritional status by measuring height of elementary school children. Analysis of data of the type with Spearman rank correlation and analysis of frequency data, the intake of energy, protein, vitamin A, and Fe intake with Pearson product moment correlation. Result : The type of animal based food that are most often consumed in a day are eggs, fish and meat (37.4%). Frequency of consumption of animal food that is most in the category <2 (51.4%). Intake of energy is at most in the category of <5% (42.9%). Intake of the most protein in enough categories (62.9%). Intake of vitamin A is at most in the category of> 10% (40%). Most Fe intake in the category <5% (54.3%). Most subjects had normal nutritional status (60%). The results of the analysis of the relationship of animal food with nutritional status showed a types p-value of 0.008, frequency p-value of 0.007, energy p-value 0.009 , protein p-value 0.003, vitamin A p-value 0.02 and Fe p-value 0.019. Conclusion : There is a relationship of animal food consumption (type, frequency, energy, vitamin A, and Fe) with the nutritional status of elementary school children of Kudu 02 Baki subdistrict Sukoharjo Regency